Association of plasminogen activator inhibitor-1 gene polymorphism and type 2 diabetic nephropathy. (2nd January 2016) - Xu, Fengbo; Liu, Huilan; Sun, Yi
Abstract: Background : We investigated the relationship between plasminogen activator inhibitor-1 (PAI-1) 4G/5G insertion/deletion polymorphism and prevalence of diabetic nephropathy (DN) in Chinese patients. Methods : A total of 107 patients with type 2 diabetes were randomly recruited in the study, and 102 healthy subjects were selected as Control. Patients were divided into three groups according to their urinary albumin–creatinine ratio (UACR). Group A ( n = 44), had patients without DN (serum creatinine <106 µmol/L and UACR <30 µg/mg); Group B ( n = 30), had patients with micro-albuminuria (UACR 30–299 µg/mg), and Group C ( n = 33), had patients with macro-albuminuria (UACR ≥300 µg/mg and creatinine <200 µmol/L). Plasma level of PAI-1 was measured by ELISA. PAI-1 polymorphism was determined by a polymerase chain reaction (PCR) method and DNA sequencing. Results : (1) The plasma PAI-1 levels of group A (60.39 ± 17.01 ng/L), group B (68.76 ± 17.81 ng/L) and group C and (68.63 ± 18.30 ng/L) are higher than that of controls (46.26 ± 26.04 ng/L); (2) Patients with genotype 4G/4G tended to exhibit higher PAI-1 level; (3) The distribution frequency of genotype 4G/4G in group C was significantly higher than in group A (42.4% vs. 28.7%, p < 0.05) and (4) In type 2 diabetic patients, the occurrence of diabetes nephropathy in genotype 4G/4G, 4G/5G and 5G/5G is 35.0%, 30.2% and 21.4%, respectively. Conclusions : (1) Plasma PAI-1 level was elevated in Type 2 diabetic patients; (2) The level of plasma PAI-1 is closely related to PAI-1 gene 4G/5G polymorphism and (3) PAI-1 4G/5G polymorphism is associated with the development and progression of predominant proteinuria diabetes nephropathy.